Self-efficacy Theory: Relevance of General and Specific Efficacy Beliefs for Psychosocial Adaptation to Chronic Illness Over Time - Rapley, Patrica (Curtin University, 2001)
Over the last decade or more, chronic illness research has consistently found that the lineaer relationship between knowledge and behaviour or between behaviour change and improved health outcomes does not exist. Furthermore, the link between behaviour and health status is not as strong as the link between illness-specific efficacy belier and health status. Strategies to increase confidence in illness-specific behaviours have gradually assumed more importance in improving health outcomes. Strategies to improve behaviour-specific efficacy belief can assist individuals to change their behaviour by influencing behavioural choices, effort and persistence with task man demands. Concomitantly, it has been suggested that there is a positive relationship between efficacy belief and psychosocial functioning. It is unclear as to whether this empirical evidence also applies to chronic illness conditions with a complex self-care regimen. The degree to which a more general level of confidence, or efficacy belief, can also contribute to psychosocial functioning is unknown. The focus of this study was to examine the relative impact of general and illness-specific efficacy expectations on psychosocial adaptation to illness over nine months. The study measured illness-specific efficacy beliefs when it was expected that they were still developing.The illness-specific beliefs were compared to the purportedly more stable general efficacy belief. This longitudinal study employed an exploratory predictive design to measure efficacy beliefs in the natural setting. Data were collected at entry to the study, at three and nine months Participants included adults from three chronic illness groups: Arthritis (n= = ), diabetes type 1 (n = 104) and type 2 (n = 122). The self-report questionnaires used collect the data were three illness-specific efficacy belief measures, general self-efficacy and the Psychosocial Adjustment to Illness Scale. The dependent variable of interest was psychosocial adaptation to illness. Multiple regression analysis provided evidence of between-group differences in the positive contribution of general and illness-specific efficacy beliefs to psychosocial adaptation for chronic illness groups with different regimen attributes. The variables best able to predict psychosocial adaptation to illness over time, after being adjusted for perceived level of stress and general self-efficacy (belief in abilities in general), were illness-specific efficacy beliefs. A general efficacy belief contributed to the illness adaptation process initially but its influence reduced as the influence of illness-specific beliefs increased. Repeated measures MANOVA confirmed the stability of general efficacy belief. The contribution of this study to current knowledge of self- -efficacy theory is its application to self-management programs for chronic illness groups. The findings suggest that the more stable general efficacy belief has a role in psychosocial adaptation to chronic illness during the period when illness-specific efficacy beliefs, targeted by self-management programs, are still developing.